Trading Data for Health - Sven Joeckel; Jakob Henke; Leyla Dogruel (University of Zurich, IKMZ - Department of Communication and Media Research, 2021)
mHealth apps are growing in popularity among smartphone users. Such apps often contain social features that enable users to compare their behavior with others but to function, mHealth apps require users to share health information which is considered a threat to individuals' privacy. Building on social comparison theory and research on privacy decision-making, we investigate the effects of users' social comparison orientation and privacy attitudes as well as the potential mediating effect of health information disclosure on users' intention to use a dietary app. Relying on a PLS-based structural-equation model in a sample of N = 528 participants, our study supports claims of a positive effect of social comparison orientation on intention to use a mHealth app. Further, the negative effect of privacy attitude and the positive mediation of information disclosure were supported as well. The study also demonstrated that findings were stable when the context of information disclosure is changed.